2021
DOI: 10.1088/2040-8986/abdf6a
|View full text |Cite
|
Sign up to set email alerts
|

Laser dynamics in nonlinear transparent media with electron plasma generation: effects of electron–hole radiative recombinations

Abstract: The performance of optical devices manufactured via laser micromachining on nonlinear transparent materials usually relies on three main factors, which are the characteristic laser parameters (i.e. the laser power, pulse duration and pulse repetition rate), the characteristic properties of host materials (e.g. their chromatic dispersions, optical nonlinearities or self-focusing features) and the relative importance of physical processes such as the avalanche impact ionization, multiphoton ionization and electr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…This means that the noise amplitudes in this case are constant and therefore the cw regime is expected to be always stable. this is consistent with the result found in [35]. Thus for k 2 > 0, satisfies laser self-starting mode regime, which is interpreted mathematically as follows:…”
Section: Continuous-waves Stability Regimesupporting
confidence: 91%
See 2 more Smart Citations
“…This means that the noise amplitudes in this case are constant and therefore the cw regime is expected to be always stable. this is consistent with the result found in [35]. Thus for k 2 > 0, satisfies laser self-starting mode regime, which is interpreted mathematically as follows:…”
Section: Continuous-waves Stability Regimesupporting
confidence: 91%
“…The minus sign at P 2 in equation (7) came from the fact that the saturable absorber effect represent the optical absorption loss. When this laser saturation power (P 2 )(power level required for achieving significant saturation of an absorber or a gain medium) goes to zero, our result is consistent with that found in [35]. To be more precised, given that equation (1) described the fact that multiphoton absorption processes will reduce or increase the threshold value of the input power needed for the laser to operate in the cw regime [36,37], depending on the characteristic values parameters of the model.…”
Section: Steady-state Solutionssupporting
confidence: 90%
See 1 more Smart Citation
“…This latter equation is characterized by two parameters namely A and B, assumed to control temperature variation in the microresonator cavity during the optical field roundtrips, as well as a source term proportional to the average power of the optical field within the cavity. By solving numerically the model equations assuming a specific ansatz [27][28][29][30][31] for the optical field, we found that an increase of the characteristic parameter A with B fixed favours an increase of the amplitude of dissipative soliton crystals. We noted that the temperature profile was not influenced by characteristic parameters in the optical-field equation, but only by those involved in the heat equation.…”
Section: Discussionmentioning
confidence: 99%
“…However, nonlinear solutions (i.e. pulse) only exist for specific values of v and ω [18,20,28]. Therefore we will only pay attention to the case of zero-velocity solutions (i.e.…”
Section: Mathematical Modelmentioning
confidence: 99%